2007
DOI: 10.1007/s00415-007-0621-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nicotine on perceptual, ocular motor, postural, and vegetative functions at rest and in motion

Abstract: Nicotine has wellknown, unpleasant side effects, e.g., transient dizziness, nausea, and nicotine-induced nystagmus (NIN). To investigate factors influencing these effects, we addressed three questions: (1) Is the intensity of dizziness, nausea, NIN, and unsteadiness dependent on nicotine dosage? (2) Does the intensity of perceptual, ocular motor, vegetative effects, and postural imbalance correlate? (3) Do visual or vestibular motion stimuli produce and/or aggravate distressing dizziness and nausea? Sixty heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 12 publications
(13 reference statements)
1
9
1
2
Order By: Relevance
“…). Moreover, it explains, on the one hand, why certain toxic effects of antiepileptics or nicotine‐induced nystagmus are directionally specific . On the other hand, transitions from UBN to DBN or DBN to UBN with head tilt, convergence, or simply during the course of the disease reflect the intricate network that maintains directional balance in the pitch plane.…”
Section: Vestibular Tone Imbalance In the Pitch Plane: Switch From Unmentioning
confidence: 99%
“…). Moreover, it explains, on the one hand, why certain toxic effects of antiepileptics or nicotine‐induced nystagmus are directionally specific . On the other hand, transitions from UBN to DBN or DBN to UBN with head tilt, convergence, or simply during the course of the disease reflect the intricate network that maintains directional balance in the pitch plane.…”
Section: Vestibular Tone Imbalance In the Pitch Plane: Switch From Unmentioning
confidence: 99%
“…It has been shown, for example, that motion increases the sensitivity to nicotine–induced nausea23. In addition, a history of motion-induced nausea is a well-recognized risk factor, not only for NVP and HG, but also for post operative nausea and chemotherapy induced nausea24.…”
Section: Commentmentioning
confidence: 99%
“…With a speed diminution in eye tracking associated to a visual stimulus. Furthermore, saccades decrease in nicotine treated animals, which is consistent with data from humans (Clarke et al 1985;Domino et al, 1997;Larrison et al, 2004;Rycroft et al;2006Zingler et al, 2007. These studies have shown that nicotine reduces the number of primary saccades during search tasks in smokers, non-smokers and in patients with schizophrenia (Avila et al, 2003;Olincy et al, 2003, Tanabe et al 2006.…”
Section: Effects Of Nicotine In the Behaviour Induced By Visual Functionsupporting
confidence: 64%
“…En los ejemplares tratados se produce una diminución de la velocidad del ojo en el seguimiento del estímulo visual asociada a la dosis de nicotina. Además disminuyen los movimientos sacádicos de los animales tratados con nicotina, lo que concuerda con lo descrito en humanos (Clarke et al, 1985;Domino et al, 1997;Larrison et al, 2004;Rycroft et al, 2006;Zingler et al, 2007). Dichos estudios han demostrado que la nicotina reduce el número de movimientos sacádicos principales durante tareas de búsqueda en fumadores, y en pacientes no fumadores con esquizofrenia (Avila et al, 2003;Olincy et al, 2003;Tanabe et al, 2006).…”
Section: Respuesta Optocinéticaunclassified